Economic Empowerment for Santri By Making Pulp Paper in Dayah of Ulumuddin, Lhokseumawe - Akhyar Ibrahim; Ilyas Yusuf; Cut Aja Rahmawati (Malikussaleh Journal of Mechanical Science and Technology, 2017)
Ulumuddin foundation situated between the coastal area and forest area is surrounded bytraditional and industry plantation. The foundation has been holding some bording school education such as SDIT, MTs, MA, and SMK, and esspecially Traditional Islamic School (Dayah). Most of santri look like lack ofliving cost because they only hope the morney from their parent who is only pre whealfers’ family. Given thesecircumstances, an effort was needed to improve the santris’ life. A partnership in technology, mentoring andcapital provision was taken through the Ipteks bagi Masyarakat (IbM) Program. A design of big blender wasprepared and introduced to two group of santri. A group of ten santri was involved to the program of makingpulp system technology aimed to increase the partners’ revenue. The results of the cost analysis concluded thatthe rate of return was 30%; the Break Event Point (BEP) was Rp.7.500/kg pulp; and return of inverment periodwas 0.6 years in-service. Copyright © 2017 Department of Mechanical Engineering. All rights reserved.